Application of SWOT Analysis and Porter’s Five Forces As a Foundation for Formulating Marketing Strategies: (Case Study of The Patuha Geothermal Area, Bandung Regency) - Putra, Muh Rifqi Ananda Putra; Pratama, Ricky Karya; Dwiyantoro, Pringgo (Journal of Mandalika Review, 2024)
Abstract Introduction: This study develops previous research by combining SWOT and Porter's Five Forces Models as a basis for determining tourism marketing strategies at the Patuha Geothermal Destination in Bandung Regency. The Patuha Geothermal Destination in Bandung Regency has become one of the geothermal tourism areas that has great potential, so this research is expected to contribute to the development of sustainable tourism. Methodology: The analytical method used is quantitative data analysis method and case studies using two well-known strategic analysis frameworks, namely SWOT Analysis (Strengths, Weaknesses, Opportunities, Threats) and Porter's Five Forces as a basis for formulating marketing strategies. Findings: The results of this research show that the SWOT results are in quadrant II so that in developing and planning the marketing of the Geothermal Patuha destination, it is necessary to implement diverse and innovative strategies as an effort to utilize internal resources and anticipate competitor threats. Apart from that, using the Porter's Five Forces approach, the appropriate strategy model for the Patuha Geothermal destination marketing strategy is to develop market penetration. Conclusion: Based on the results of the analysis using Porter's Five Forces approach, the recommended strategy for maintaining Patuha Geothermal tourism potential is through an intensive approach with market development strategies that involve more active promotional activities and offering more competitive prices to visitors. Keywords: SWOT Analysis, Porter's Five Forces Model, Marketing Strategy